Thucydides at sea Chinese perspectives on international law and the South China Sea dispute in an evolving international order (Philippine Law Journal, 2022)
Five years after Philippines v. China, China's great power domination in the South China Sea ("SCS") remains a reality. Chinese maritime aggression has aggression in full force, with repeated provocations heightening insecurities in the world's most contested maritime region. This Article dives into the People's Republic of China's evolving great power approach to international law and its implications for the SCS disputes that significantly threaten international economic and security interests. It first sketches the role and constraints posed by China's historical approaches to international relations and party-state politics, before describing the key developments that led to the SCS Arbitration and discussing salient points of the Arbitral Award on the legal status of certain maritime features. Finally, the Article examines China's reception of and compliance with the Award and shows why emergent Chinese legalism and global leadership ambitions may prove insufficient in promoting pacific resolution of these disputes